Pelatihan Pembuatan Wingko Untuk Mengembangkan Keterampilan Kader PKK Desa Kranji Paciran, Lamongan - Erly Juliyani; Pusvyta Sari (Annusfy : Journal of Multidisciplinary Research, 2026)
Skills training is one way to develop human resources. Similarly, this community service activity—namely, a wingko-making training program—was organized to improve the skills of Family Empowerment and Welfare (PKK) cadres in Kranji Village, Paciran Subdistrict, Lamongan Regency, in making wingko, a culinary product that serves as a signature souvenir of Lamongan Regency. As a village located near religious and educational tourist areas, processed foods as souvenirs hold good economic prospects. This training method consists of planning and preparation, training implementation, and evaluation. The training was enthusiastically attended by the PKK cadres of Kranji Village and served to boost motivation while inspiring creative ideas to optimize the village’s potential and develop businesses by leveraging the skills they possess.